1999
DOI: 10.1177/00238309990420010101
|View full text |Cite
|
Sign up to set email alerts
|

A Cross- Linguistic Study in Learning Prosodic Rhythms: Rules, Constraints, and Similarity

Abstract: Differences in the learnability of linguistic patterns may be crucial in deciding among alternative learning models. This paper compares the ability of English speakers (Experiment1) and Portuguese speakers (Experiment 2) to learn two complex rhythm patterns observed in languages with primary word stress. Subjects were familiarized with one of two rhythms during a discrimination task, followed by a recognition task which tested whether knowledge of the rhythm generalized to novel stimuli. The main findings wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 29 publications
(50 reference statements)
1
12
0
Order By: Relevance
“…The fact that both groups of Turkish L2 learners benefit from L1 and L2 rhythmic diversity seems to indicate that L2 speakers are sensitive and may learn, to some degree, L2 rhythmic properties beyond a sensitive period (Bailey et al, 1999; Goetry and Kolinsky, 2000; Field, 2003; Trofimovich and Baker, 2006). …”
Section: Discussionmentioning
confidence: 99%
“…The fact that both groups of Turkish L2 learners benefit from L1 and L2 rhythmic diversity seems to indicate that L2 speakers are sensitive and may learn, to some degree, L2 rhythmic properties beyond a sensitive period (Bailey et al, 1999; Goetry and Kolinsky, 2000; Field, 2003; Trofimovich and Baker, 2006). …”
Section: Discussionmentioning
confidence: 99%
“…However, only a few studies have focused on whether implicit knowledge of stress rules can be acquired. Bailey, Plunkett, and Scarpe (1999) conducted a cross-linguistic study on the learnability of rhythm patterns. They found that knowledge of complex stress patterns can be generalized even after only brief exposure, and that typologically less common stress patterns were easier to learn.…”
Section: Acquiring Implicit Knowledge Of Lexical Stress Patternsmentioning
confidence: 99%
“…Despite the many studies on classroom interactions, few have provided a clear account of turn-taking strategies, and yet turn-taking is a basic form of organization for conversation (Oreström, 1983;Roger, Bull, & Smith, 1988;Bailey, Plunkett & Scarpa, 1999;Schegloff, 2000;Bortfeld, Leon, Bloom, Schober, & Brennan, 2001). Turn-taking maintains a mutual attention among parties involved in a conversation, defines their relationship (Wiemann & Knapp, 1999) and the pertinence boundaries related to interaction (Kendon, 1992).…”
Section: Theoretical Frameworkmentioning
confidence: 99%